The Insistence of the Indian : Race and Nationalism in Nineteenth-Century American Culture - Scheckel, Susan (Book collections on Project MUSE., 2001)
Americans' first attempts to forge a national identity coincided with the apparent need to define--and limit--the status and rights of Native Americans. During these early decades of the nineteenth century, the image of the "Indian" circulated throughout popular culture--in the novels of James Fenimore Cooper, plays about Pocahontas, Indian captivity narratives, Black Hawk's autobiography, and visitors' guides to the national capitol. In exploring such sources as well as the political and legal rhetoric of the time, Susan Scheckel argues that the "Indian question" was intertwined with the ways.